Integration, participation and optimal control in water resources planning and management - Castelletti, Andrea; Pianosi, Francesca; Soncini-Sessa, Rodolfo (Applied mathematics and computation, 2008)
Water resource systems provide a challenging testing ground for System Analysis and Optimal Control Theory. The intrinsic complexity of the physical system, which is highly non-linear and affected by strong uncertainty, intermingles with the value-laden socio-economic context in which decisions on the systems have to be taken. Mathematical models and algorithms have to be re-considered within a methodological framework, in which stakeholder participation and cross-disciplinary approaches are given a central role. In this paper the Integrated and Participatory Planning (PIP) procedure developed by the authors is presented as a potential methodological approach to the effective and efficient planning and management of water systems. Great emphasis is given to the way to combine traditional control techniques with preference and subjective aspects of decision-making. The key role of Multi-Objective Decision Support Systems (MODSS) is also stressed as a way of bridging the gap between theory and practice.